DISTRIBUTION AND DIVERSITY OF BIVALVIANS IN THE INTERTIDAL ZONE REGION OF VILLAGE ANAK SETATAH, KEPULAUAN MERANTI REGENCY - Wafa, Khairuw; Thamrin, Thamrin; Nasution, Syafruddin (Asian Journal of Aquatic Sciences, 2023)
This study was conducted from May to June 2022 to know the species, abundance, diversity, and distribution patterns in the tidal areas of Anak Setatah Village. As supporting data in this study, several environmental parameters were also measured, including water quality, sediment type, and sediment organic matter content. The study method was a survey method, where sampling used the quadrat transect method. The results found that there were three species of bivalves. Where the abundance among stations ranged from 0.49 to 0.74 and/m2. The value of the species diversity index ranged from 0.91 to 1.41, which was classified as moderate, and the matter of the distribution pattern ranged from 6.28 to 9.71 with a clumped distribution pattern.